Comparative outcomes of open and arthroscopic approaches for recurrent anterior shoulder instability - Suraj Verma, Buddharaju; Ashok, Padala; Mahesh Chandra, Suvvari (International Journal of Research in Orthopaedics, 2025)
Background: A prominent orthopedic ailment that severely impairs function and lowers quality of life in young, energetic people is recurrent anterior shoulder instability. Surgical intervention is often required to restore stability and prevent repeated dislocations. Open Latarjet and arthroscopic Bankart repair are the two widely employed techniques, but comparative outcomes remain debated. Aim was to evaluate the clinical and functional results of open surgery against arthroscopic surgery in the past for patients with recurrent anterior shoulder instability. Methods: A retrospective study was conducted at the Department of Orthopaedics, NRI Institute of Medical Sciences, Sangivalasa, Visakhapatnam, from May 2023 to April 2025. A total of 30 patients with recurrent anterior shoulder instability were included, with 15 undergoing open surgical repair and 15 receiving arthroscopic repair. Data on demographics, clinical presentation, surgical procedure, functional outcomes (Rowe and Constant-Murley scores), recurrence, and complications were collected from hospital records. SPSS version 23.0 was used for the statistical analysis, and a p-value of less than 0.05 was deemed significant. Results: Both open and arthroscopic groups demonstrated significant postoperative improvement in functional scores. The mean Rowe score was 85.4±6.8 in the open group and 88.1±5.9 in the arthroscopic group (p=0.28), while the Constant-Murley score was 82.6±7.2 and 85.3±6.7, respectively (p=0.31). Recurrent instability occurred in 20% of the open group and 13.3% of the arthroscopic group (p=0.63). Complications such as stiffness and superficial infection were slightly higher in the open group, However, there were no statistically significant variations. Conclusions: Recurrent anterior shoulder instability can be effectively managed with both open and arthroscopic surgical procedures providing excellent functional recovery and low recurrence rates. Arthroscopic repair demonstrated marginally better functional outcomes and fewer complications, but differences were not statistically significant. The choice of surgical technique should be individualized based on patient characteristics, extent of glenoid bone loss, activity level, and surgeon expertise. Both procedures remain reliable options for restoring shoulder stability.